Le pagne - Raoul Germain Blé (Communication)
African women use printed cotton to make garments such as loincloths. These printed loincloths can be viewed as carrying social messages, anywhere from the cultural identity and social position of the wearer to the proclamation of “neo-africanism.” Because the printed cotton makes up so much of the daily wear, the “messages” they carry can be interpreted as so many “news flashes” of the day.